A Novel Pharmacological Method to Study the Chinese Medicinal Formula Hua-Zheng-Hui-Sheng-Dan. (1st September 2015) - Cao, Rui; Zhang, Hong; Guo, Jie; Liu, Xiao-hui; Liu, Chang; Zhu, Cui-hong; Wu, Xiong-zhi
Abstract : Objectives . Hua-Zheng-Hui-Sheng-Dan (HZHSD) was used as an experimental model to explore research methods of large formulae in traditional Chinese medicine (TCM) using current molecular biology approaches. Materials and Methods . The trypan blue exclusion assay was used to determine cell viability and cell numbers. Flow cytometry was used to assess cell cycle distribution and apoptosis. The concentration of cyclin D1 was analyzed by enzyme-linked immunosorbent assay. The median effect principle was used in drug combination studies. An orthogonal experimental design was used to estimate the effects of each herb at different concentrations. The HeLa xenograft mouse model was used to compare the antitumor activity of drugs in vivo. Results . Among the 35 herbs that comprise HZHSD, Radix Rehmanniae Preparata (RRP), Caesalpinia sappan (CS), Evodia rutaecarpa (ER), Folium Artemisiae Argyi (FAA), Leonurus japonicus Houtt (LJH), Tumeric (Tu), Radix Paeoniae Alba (RPA), and Trogopterus Dung (TD) effectively inhibited the proliferation of HeLa and SKOV3 cells. Only RRR had an effect on HeLa and SKOV3 cell viability. According to the median effect principle, Angelica sinensis (Oliv.) (AS), Tabanus (Ta), and Pollen Typhae (PT), which were proven to have a significant synergistic inhibitory effect on the proliferation of HeLa cells, were added to the original eight positive herbs. The combination of RPA and AS had a synergistic effect on inducing cell cycle S phase arrest and decreasing intracellular cyclin D1 in HeLa cells. By orthogonal experimental design, LJH and Tu were considered unnecessary herbs. The small formula (SHZHSD) consisted of RPA, AS, RRR, Ta., TD, PT, ER, CS, and FAA and was able to inhibit cell proliferation and induce cell apoptosis. The antitumor effects of HZHSD and SHZHSD were also compared in vivo. Conclusions . Through molecular biology approaches both in vitro and in vivo, research into single drugs, and analysis using the median effect principle and orthogonal experimental design, the small formula (SHZHSD) was determined from the original formula (HZHSD). SHZHSD exhibited superior antitumor activity compared with the original formula both in vitro and in vivo.